Analisis Manajemen Risiko terhadap Keselamatan dan Kesehatan Kerja (K3) dengan Metode HIRARC di Pelabuhan Tanjung Perak - Vella Sephia Arianto; Syadzadhiya Qothrunada Z (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The port industry plays an important role in Indonesia's economic growth, but its operational activities pose a major risk to occupational safety and health (OHS). The aim is to analyze the management of occupational accident risk hazards at Tanjung Perak Port. And identify potential hazards in loading and unloading activities, use of heavy equipment, and worker safety. This study was conducted qualitatively, which showed that several risks were in the low category with 2 risks, medium with 25 risks, and high with 12 risks, so that these results require immediate control measures. The application of OHS management through the HIRARC method helps to systematically identify, assess, and control hazards. This study suggests increasing compliance with the use of personal protective equipment (PPE), optimizing work procedures, and regular safety training to significantly reduce occupational accidents.